Vocational education and training, innovation and globalisation - Curtain, Richard [Verfasser] (National Centre for Vocational Education Research, 2004)
"Innovation, from high profile scientific discoveries to lower profile changes in processes or practices, is crucial to Australia's economic development. However, its impact on the wider community is usually relatively small. Promotion of innovation across all sectors is required to produce the biggest changes. This report focuses on the roles of the vocational education and training (VET) sectors of Finland and Singapore - countries with strong track records in innovation. It argues that a whole-of-government approach supporting a national innovation system could benefit Australia. Further, the national VET sector is ideally placed to have a more direct role in the promotion and diffusion of smaller scale innovations provided incentives in the form of specific funding are put in place. This activity could also enhance the sector's links with business, particularly small to medium sized enterprises and those in regional areas. Appended are: (1) Finland: New linkages between vocational education and training and a national innovation system; (2) Singapore: The high skills path to a knowledge economy; and (3) List of interviewees on Australia's national innovation system and the implications for vocational education and training." (ERIC)
Keywords: Berufsbildungspolitik; Bildungspolitik; Innovationsprozess; Globalisierung; Wissensgesellschaft; Finnland; Singapur; Australien